Vegetable oil-based epoxy coating materials for self-healing and anticorrosive applications - (:unkn) unknown (My University, 2023)
A new bio-based epoxy curing agent from hempseed oil was prepared in this study. The chemical structure of the curing agent was confirmed by infrared spectrometry and nuclear magnetic resonance. Soybean oil-based epoxy resin was cured with a hempseed oil-based green curing agent to prepare a series of sustainable coatings under eco-friendly conditions. The reaction of epoxy resin with anhydride groups reacted without a catalyst. The prepared sustainable coatings showed excellent scratching and adhesion resistance. In addition, the coating showed self-healing properties via dynamic transesterification bonds between the epoxy and anhydride groups. The corrosion resistance of the sustainable coatings is investigated using electrochemical measurements. It revealed that the materials have strong anti-corrosion performance. Hence, these coatings can be used as a green alternative for encapsulation-based corrosion protection systems. Furthermore, the produced materials could be used as a VOC-free coating system. Graphical abstract: A catalyst-free and environmentally friendly method was developed for the preparation of epoxy materials. The creation of bio-based epoxy hardener agents using greener techniques is a significant issue. The development of fully sustainable materials from non-edible vegetables is an attractive strategy to minimize the risk to human health and the environment.[Figure not available: see fulltext.]
Keywords: Kimya Mühendisliği ve Teknolojisi; Kimya; Biyokimya; Biyoinorganik Kimya; Fizikokimya; Polimer Karakterizasyonu; Temel Bilimler; Mühendislik ve Teknoloji; Chemical Engineering and Technology; Chemistry; Biochemistry; Bioinorganic Chemistry; Physical Chemistry; Characterization of Polymers; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Mühendislik; Malzeme Bilimi; MÜHENDİSLİK, KİMYASAL; POLİMER BİLİMİ; KİMYA, ORGANİK; MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); ENGINEERING; MATERIALS SCIENCE; CHEMISTRY; ENGINEERING, CHEMICAL; POLYMER SCIENCE; CHEMISTRY, ORGANIC; MATERIALS SCIENCE, MULTIDISCIPLINARY; Genel Kimya Mühendisliği; Fizik Bilimleri; Organik Kimya; Polimerler ve Plastikler; Malzeme Kimyası; General Chemical Engineering; Physical Sciences; Organic Chemistry; Polymers and Plastics; Materials Chemistry; Anticorrosive coating-self-healing; Bio-based material